Magnesium-aluminum alloy casting coating and preparation process

By using a combination of base coating and top coating in magnesium alloy casting, combined with specific raw material ingredients and processes, the problems of fast cooling speed and slow curing speed during the casting process are solved, and high-quality production and production efficiency of castings are improved.

CN119657818APending Publication Date: 2025-03-21SWISS AIRLINES (JIANGSU) NEW MATERIAL TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411933911.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the casting process of magnesium alloy, existing casting coatings have problems such as single thermal insulation function, fast cooling speed, local early crystallization, slow curing speed, and uneven drying.

Method used

The combination of base coating and top coating is used. The base coating is mixed with magnesium sand powder and refractory aggregate of specific particle size, and the top coating contains aggregate of specific particle size. The alcohols are evaporated by ignition, releasing continuous and widespread heat, delaying the cooling rate of the casting, and using combustion waste heat to accelerate the curing reaction of the top coating.

Benefits of technology

Effectively delay the cooling speed of magnesium-aluminum alloy castings, improve the curing speed and uniformity of the coating, ensure the consistency and reliability of the coating performance, avoid local advance crystallization, and improve the overall performance and production efficiency of the castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657818A_ABST
    Figure CN119657818A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium-aluminum alloy casting coating and a preparation process thereof. The casting coating comprises a prime coating and a surface coating, the prime paint is prepared from the following raw materials in parts by mass: prime aggregate, an alcohol solvent, a flatting agent and a dispersing agent; the bottom layer aggregate is mixed aggregate of magnesia powder and refractory aggregate; the surface layer coating is prepared from the following raw materials in parts by mass: surface layer aggregate, a binder, a suspending agent, a dispersing agent and water. According to the casting coating disclosed by the invention, magnesia powder adopted by the prime coating is mixed with refractory aggregate with a specific particle size, aggregate with a specific particle size is adopted by the surface coating, and the curing speed and uniformity of the coating are improved through the synergistic effect of the prime coating and the surface coating in combination with specific raw material proportioning and process; the consistency and the reliability of the coating performance are ensured, the problems of high cooling speed and local advanced crystallization in the magnesium alloy casting process are effectively solved, and the overall performance and the production efficiency of castings are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of casting modeling, in particular to a casting mold surface coating, specifically a magnesium-aluminum alloy casting coating and a preparation process thereof. Background Art

[0002] In the field of metal casting, magnesium-aluminum alloys are widely used in aerospace, automobile manufacturing, electronic communications and other industries due to their low density, high strength-to-weight ratio and good mechanical properties. During the casting process, magnesium-aluminum alloys have a relatively low melting point and good thermal conductivity, resulting in very fast cooling during the casting process. This rapid cooling often causes stress inside the casting, which in turn causes defects such as cracks and deformation. In addition, due to the uneven cooling rate, various parts of the casting may experience local premature crystallization, resulting in uneven structure and performance of the casting, which may even affect the performance of the casting in severe cases.

[0003] In order to solve the above problems, the foundry industry usually applies a layer of casting coating on the surface of magnesium alloy castings. The casting coating can not only play a heat insulation role and slow down the cooling rate of the casting, but also improve the surface quality of the casting and increase the yield rate of the casting. However, the existing casting coating still has some shortcomings in the magnesium alloy casting process.

[0004] On the one hand, existing casting coatings often only have a single heat insulation function and cannot provide additional heat during the casting process to further slow down the cooling rate of the casting. As a result, the casting is still prone to problems such as rapid cooling and partial premature crystallization during the casting process.

[0005] On the other hand, existing casting coatings, such as conventional water-based coatings, often take a long time to completely dry and solidify during the coating process, and have problems such as slow curing speed and uneven drying. This not only affects the casting efficiency, but may also cause the coating to form an uneven coating on the surface of the casting, thereby affecting the quality of the casting.

[0006] Therefore, it is necessary to improve the deficiencies in the prior art to solve the above problems. Summary of the invention

[0007] The invention overcomes the shortcomings of the prior art and provides a magnesium-aluminum alloy casting coating and a preparation process.

[0008] To achieve the above object, the technical solution adopted by the present invention is: a magnesium-aluminum alloy casting coating, comprising: a primer and a surface coating, characterized in that: the mass ratio of the primer to the surface coating is 1:1-2;

[0009] The primer comprises the following raw materials in parts by weight:

[0010]

[0011] The surface coating comprises the following raw materials in parts by weight:

[0012]

[0013] The bottom layer aggregate is a mixed aggregate of magnesia powder and refractory aggregate, and the particle size of the refractory aggregate is larger than that of the surface layer aggregate.

[0014] In a preferred embodiment of the present invention, the refractory aggregate accounts for 30-50% of the total amount of the bottom aggregate, for example, it can be 30%, 35%, 40%, 45% or 50%, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the refractory aggregate is one of expanded perlite, hollow microspheres, mullite or zircon powder; the particle size of the refractory aggregate is 170-200 mesh, for example, it can be 170 mesh, 175 mesh, 180 mesh, 185 mesh, 190 mesh, 195 mesh or 200 mesh, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0015] In a preferred embodiment of the present invention, the surface layer aggregate is one of mullite powder, corundum powder or zircon powder; the particle size of the surface layer aggregate is 270-325 mesh, for example, it can be 270 mesh, 280 mesh, 285 mesh, 290 mesh, 300 mesh, 305 mesh, 310 mesh, 315 mesh or 325 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] In a preferred embodiment of the present invention, the alcohol solvent is one of methanol or ethanol.

[0017] In a preferred embodiment of the present invention, the leveling agent is one of silicone oil, polyacrylate or polysiloxane.

[0018] In a preferred embodiment of the present invention, the dispersant is one of polyethylene glycol or sodium polyacrylate.

[0019] In a preferred embodiment of the present invention, the binder is one of aluminum dihydrogen phosphate or phenolic resin.

[0020] In a preferred embodiment of the present invention, the suspending agent is one of sodium bentonite, sodium carboxymethyl cellulose or hydroxyethyl cellulose.

[0021] The present invention provides a preparation process of a magnesium-aluminum alloy casting coating, comprising the following steps:

[0022] S1, adding magnesia powder and refractory aggregate into a planetary ball mill for ball milling and mixing to obtain bottom aggregate;

[0023] S2, adding the bottom aggregate, alcohol solvent, leveling agent and dispersant into a planetary ball mill for ball milling and mixing to obtain a bottom coating;

[0024] S3. Add the surface layer aggregate, binder, suspending agent, dispersant and water into a planetary ball mill for wet grinding and mixing to obtain the surface layer coating.

[0025] In a preferred embodiment of the present invention, in the step S1 and the step S2, the mixing speed of the ball mill is 180-220 r / min, for example, it can be 180 r / min, 190 r / min, 200 r / min, 210 r / min or 220 r / min, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The mixing time is 30-50 min, for example, it can be 30 min, 35 min, 40 min, 45 min or 50 min, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The same is applicable; in the S3 step, the mixing speed of the wet grinding is 200-240r / min, for example, it can be 200r / min, 210r / min, 220r / min, 230r / min or 240r / min, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. The mixing time is 30-60min, for example, it can be 30min, 35min, 40min, 45min, 50min, 55min or 60min, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0027] (1) The present invention provides a magnesium-aluminum alloy casting coating and a preparation process. The casting coating of the present invention is composed of a base coating and a surface coating. The magnesia powder used in the base coating is mixed with a refractory aggregate of a specific particle size, and the surface coating has an aggregate of a specific particle size. After coating the base coating, the alcohol therein is volatilized by ignition, thereby releasing continuous and extensive heat. This not only effectively slows down the cooling rate of the magnesium-aluminum alloy casting, but also accelerates the curing reaction of the surface coating by utilizing the residual heat of combustion, thereby achieving rapid curing and uniform drying of the coating. Thus, through the synergistic effect of the base coating and the surface coating, combined with specific raw material formulations and processes, not only the curing rate and uniformity of the coating are improved, the consistency and reliability of the coating performance are ensured, but also the defects of fast cooling rate and local premature crystallization in the magnesium alloy casting process are effectively solved, thereby improving the overall performance and production efficiency of the casting.

[0028] (2) In the present invention, the refractory aggregate in the base coating and the surface aggregate in the surface coating are made of specific particle sizes, and the particle size of the refractory aggregate is larger than that of the surface aggregate. The large-particle refractory aggregate not only increases the porosity of the coating, but also reduces the density of solid components such as aggregate and binder, so that the same volume of coating can contain more alcohol solvents, thereby releasing more heat and longer residual heat time during combustion, providing the required thermal conditions for the curing of the surface coating. The small-particle surface aggregate reduces the gaps between the aggregate particles in the coating, reduces the content of bound water, and accelerates the drying speed of the coating. Therefore, under the synergistic effect of the base coating and the surface coating, not only the curing speed and uniformity of the coating are improved, but also the risk of local premature crystallization is effectively avoided by slowing down the cooling rate of the magnesium-aluminum alloy casting, thereby ensuring the high-quality production of the casting.

[0029] (3) In the present invention, by making the particle size of the refractory aggregate in the base coating larger than the particle size of the surface layer aggregate in the surface coating, the surface layer aggregate can fill the larger gaps left by the refractory aggregate, thereby reducing the interface gap between the base coating and the surface coating, so that the interface between the two can form a mechanical interlocking, increase the friction between the base coating and the surface layer, thereby improving the overall density and bonding strength, helping to form an overall uniform coating and reduce local defects.

[0030] (4) In the present invention, expanded perlite with a porous structure or hollow microspheres with a hollow structure are used as refractory aggregates in the base coating. By utilizing their unique structure, more alcohol solvents can be effectively stored. When combustion occurs, not only can the temperature rise rapidly and release a large amount of heat, but also due to their lightweight characteristics, the heat transfer is more uniform, reducing the impact of temperature gradients on castings, helping to form a more stable base coating, thereby improving the mechanical interlocking between the base coating and the surface coating, and enhancing the bonding strength of the overall coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 The present invention is a flow chart of a process for preparing a magnesium-aluminum alloy casting coating according to a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0035] It should be noted that the raw materials, equipment and reagents used in the present invention can be purchased from the market or obtained through the preparation methods of existing technologies.

[0036] like Figure 1 As shown, a magnesium-aluminum alloy casting coating comprises: a primer coating and a surface coating, wherein the mass ratio of the primer coating to the surface coating is 1:1-2;

[0037] The base coating comprises the following raw materials in parts by weight:

[0038]

[0039] The surface coating comprises the following raw materials in parts by weight:

[0040]

[0041] The bottom layer aggregate is a mixture of magnesia powder and refractory aggregate, and the particle size of the refractory aggregate is larger than that of the surface layer aggregate.

[0042] In some specific implementations, the refractory aggregate accounts for 30-50% of the total amount of the bottom aggregate; the refractory aggregate is one of expanded perlite, hollow microspheres, mullite or zircon powder; and the particle size of the refractory aggregate is 170-200 meshes.

[0043] In some specific embodiments, the surface layer aggregate is one of mullite powder, corundum powder or zircon powder; and the particle size of the surface layer aggregate is 270-325 mesh.

[0044] In some specific embodiments, the alcohol solvent is one of methanol or ethanol.

[0045] In some specific embodiments, the leveling agent is one of silicone oil, polyacrylate or polysiloxane.

[0046] In some specific embodiments, the dispersant is one of polyethylene glycol or sodium polyacrylate.

[0047] In some specific embodiments, the binder is one of aluminum dihydrogen phosphate or phenolic resin.

[0048] In some specific embodiments, the suspending agent is one of sodium bentonite, sodium carboxymethyl cellulose or hydroxyethyl cellulose.

[0049] like Figure 1 As shown, the present invention provides a preparation process of a magnesium-aluminum alloy casting coating, comprising the following steps:

[0050] S1, adding magnesia powder and refractory aggregate into a planetary ball mill for ball milling and mixing to obtain bottom aggregate;

[0051] S2, adding the bottom aggregate, alcohol solvent, leveling agent and dispersant into a planetary ball mill for ball milling and mixing to obtain a bottom coating;

[0052] S3. Add the surface layer aggregate, binder, suspending agent, dispersant and water into a planetary ball mill for wet grinding and mixing to obtain the surface layer coating.

[0053] In some specific embodiments, in step S1 and step S2, the mixing speed of ball milling is 180-220 r / min, and the mixing time is 30-50 min; in step S3, the mixing speed of wet milling is 200-240 r / min, and the mixing time is 30-60 min.

[0054] The following is a detailed description of the overall implementation of the present invention in conjunction with specific examples.

[0055] The base coating raw materials and surface coating raw materials of Examples 1-7, as well as the raw material ratios are different, as shown in Table 1 and Table 2, and the raw materials are measured by mass.

[0056] Table 1: Raw materials and proportions for the preparation of base coating materials

[0057]

[0058]

[0059] Table 2: Raw materials and proportions for the preparation of surface coating materials

[0060]

[0061] Example 1

[0062] A preparation process of a magnesium-aluminum alloy casting coating comprises the following steps:

[0063] S1. Add magnesia powder and expanded perlite into a planetary ball mill, and mix them at a speed of 200 r / min for 45 min to obtain a bottom aggregate;

[0064] S2, adding the bottom aggregate, methanol, polyacrylate and polyethylene glycol into a planetary ball mill, and mixing them at a speed of 200 r / min for 45 minutes to obtain a bottom coating;

[0065] S3. Add mullite powder, aluminum dihydrogen phosphate, sodium carboxymethyl cellulose, polyethylene glycol and water into a planetary ball mill, and wet-grind and mix at a speed of 225 r / min for 50 min. Adjust the Baume degree to obtain the surface coating.

[0066] Wherein, in step S1, magnesia powder accounts for 60% of the total amount of the bottom aggregate, and expanded perlite accounts for 40% of the total amount of the bottom aggregate; the particle size of the expanded perlite is 180 meshes; in step S3, the particle size of the mullite powder is 300 meshes.

[0067] Example 2

[0068] This embodiment is basically the same as embodiment 1, except that the raw materials and proportions are different, as shown in Table 1 and Table 2; specifically, the following steps are included:

[0069] S1. Add magnesia powder and expanded perlite into a planetary ball mill, and mix them at a speed of 180 r / min for 50 min to obtain a bottom aggregate;

[0070] S2, adding the bottom aggregate, methanol, silicone oil and polyethylene glycol into a planetary ball mill, and mixing them at a speed of 180 r / min for 50 minutes to obtain a bottom coating;

[0071] S3. Add mullite powder, aluminum dihydrogen phosphate, sodium bentonite, sodium polyacrylate and water into a planetary ball mill, mix them at a speed of 240 r / min for 30 minutes, and adjust the Baume degree to obtain the surface coating.

[0072] Wherein, in step S1, magnesia powder accounts for 50% of the total amount of the bottom aggregate, and expanded perlite accounts for 50% of the total amount of the bottom aggregate; the particle size of the expanded perlite is 175 mesh; in step S3, the particle size of the mullite powder is 300 mesh.

[0073] Example 3

[0074] This embodiment is basically the same as embodiment 1, except that the raw materials and proportions are different, as shown in Table 1 and Table 2; specifically, the following steps are included:

[0075] S1. Add magnesia powder and expanded perlite into a planetary ball mill, and mix them at a speed of 200 r / min for 45 min to obtain a bottom aggregate;

[0076] S2, adding the bottom aggregate, ethanol, silicone oil and polyethylene glycol into a planetary ball mill, and mixing them at a speed of 200 r / min for 45 minutes to obtain a bottom coating;

[0077] S3. Add zircon powder, aluminum dihydrogen phosphate, sodium bentonite, polyethylene glycol and water into a planetary ball mill, and wet-grind and mix at a speed of 210 r / min for 50 min. Adjust the Baume degree to obtain the surface coating.

[0078] Wherein, in step S1, magnesia powder accounts for 70% of the total amount of the bottom aggregate, and expanded perlite accounts for 30% of the total amount of the bottom aggregate; the particle size of the expanded perlite is 170 mesh; in step S3, the particle size of the mullite powder is 270 mesh.

[0079] Example 4

[0080] This embodiment is basically the same as embodiment 1, except that the raw materials and proportions are different, as shown in Table 1 and Table 2; specifically, the following steps are included:

[0081] S1. Add magnesia powder and expanded perlite into a planetary ball mill, and mix them at a speed of 200 r / min for 45 min to obtain a bottom aggregate;

[0082] S2, adding the bottom aggregate, methanol, polysiloxane and sodium polyacrylate into a planetary ball mill, and mixing them at a speed of 200 r / min for 45 minutes to obtain a bottom coating;

[0083] S3. Add zircon powder, phenolic resin, sodium carboxymethyl cellulose, polyethylene glycol and water into a planetary ball mill, mix them at a speed of 225 r / min for 50 min, and adjust the Baume degree to obtain the surface coating.

[0084] Wherein, in step S1, magnesia powder accounts for 70% of the total amount of the bottom aggregate, and expanded perlite accounts for 30% of the total amount of the bottom aggregate; the particle size of the expanded perlite is 200 mesh; in step S3, the particle size of the mullite powder is 325 mesh.

[0085] Example 5

[0086] This embodiment is basically the same as embodiment 1, except that the raw materials and proportions are different, as shown in Table 1 and Table 2; specifically, the following steps are included:

[0087] S1. Add magnesia powder and expanded perlite into a planetary ball mill, and mix them at a speed of 200 r / min for 45 min to obtain a bottom aggregate;

[0088] S2, adding the bottom aggregate, ethanol, polyacrylate and sodium polyacrylate into a planetary ball mill, and mixing them at a speed of 200 r / min for 45 minutes to obtain a bottom coating;

[0089] S3. Add corundum powder, phenolic resin, hydroxyethyl cellulose, polyethylene glycol and water into a planetary ball mill, mix them at a speed of 225 r / min for 50 min, and adjust the Baume degree to obtain the surface coating.

[0090] Wherein, in step S1, magnesia powder accounts for 65% of the total amount of the bottom aggregate, and expanded perlite accounts for 35% of the total amount of the bottom aggregate; the particle size of the expanded perlite is 180 mesh; in step S3, the particle size of the mullite powder is 325 mesh.

[0091] Example 6

[0092] This embodiment is basically the same as embodiment 1, except that the raw materials and proportions are different, as shown in Table 1 and Table 2; specifically, the following steps are included:

[0093] S1. Add magnesia powder and expanded perlite into a planetary ball mill, and mix them at a speed of 220 r / min for 30 min to obtain a bottom aggregate;

[0094] S2, adding the bottom aggregate, ethanol, silicone oil and polyethylene glycol into a planetary ball mill, and mixing them at a speed of 220 r / min for 30 minutes to obtain a bottom coating;

[0095] S3. Add corundum powder, aluminum dihydrogen phosphate, sodium carboxymethyl cellulose, sodium polyacrylate and water into a planetary ball mill, and wet-grind and mix at a speed of 240 r / min for 30 minutes. Adjust the Baume degree to obtain the surface coating.

[0096] Wherein, in step S1, magnesia powder accounts for 60% of the total amount of the bottom aggregate, and expanded perlite accounts for 40% of the total amount of the bottom aggregate; the particle size of the expanded perlite is 170 meshes; in step S3, the particle size of the mullite powder is 325 meshes.

[0097] Example 7

[0098] This embodiment is basically the same as embodiment 1, except that the raw materials and proportions are different, as shown in Table 1 and Table 2; specifically, the following steps are included:

[0099] S1. Add magnesia powder and expanded perlite into a planetary ball mill, and mix them at a speed of 200 r / min for 45 min to obtain a bottom aggregate;

[0100] S2, adding the bottom aggregate, methanol, polyacrylate and sodium polyacrylate into a planetary ball mill, and mixing them at a speed of 200 r / min for 45 minutes to obtain a bottom coating;

[0101] S3. Add zircon powder, phenolic resin, hydroxyethyl cellulose, polyethylene glycol and water into a planetary ball mill, mix them at a speed of 225 r / min for 50 min, and adjust the Baume degree to obtain the surface coating.

[0102] Wherein, in step S1, magnesia powder accounts for 70% of the total amount of the bottom aggregate, and expanded perlite accounts for 30% of the total amount of the bottom aggregate; the particle size of the expanded perlite is 175 meshes; in step S3, the particle size of the mullite powder is 270 meshes.

[0103] Performance testing: The base coating and top coating obtained in the above Examples 1-7 were subjected to a performance test of the drying speed of the top coating on the base coating; at the same time, performance tests of strength, viscosity, suspension and leveling were carried out in sequence.

[0104] Drying speed test of surface coating: apply the base coating on the sand block, ignite and dry, immediately spray the surface coating, observe and record the drying time of the coating; the mass ratio of the base coating to the surface coating is 1:1.5.

[0105] Strength test: refer to the falling sand method, the specific test process is: place the Tu 4 viscosity cup at a distance of 1000mm from the coated glass sheet (the same coating method as the surface coating drying speed test), and the glass sheet is tilted to form a 45° angle with the horizontal plane. The Tu 4 viscosity cup is filled with sand. During the measurement, the viscosity cup drops sand on the coated glass sheet until a circular hole of about 2-4mm appears on the glass sheet. Collect the fallen sand, weigh the total mass as a performance indicator for judging the strength of the coating, and take the average of the three test values.

[0106] Viscosity test: Use SNB-4 digital viscometer, pour the paint to be tested into the beaker, so that the paint liquid level should just cover the rotor notch to ensure accurate measurement. Select rotor No. 2 for viscosity measurement. Place the rotor and protection frame on the instrument, select the required rotor and speed to start measurement.

[0107] Suspension test: Referring to the standard measuring cylinder method GB / T5107-2008, stir 100ml of the paint evenly, then pour it into a 25mm×100ml measuring cylinder to reach the 100ml mark. After standing for 24 hours, observe the stratification in the measuring cylinder. The proportion of the suspension in the measuring cylinder is the suspension of the paint.

[0108] Leveling test: Use a viscosity cup as a sample tube, place it about 10 cm above the glass plate, use a measuring cylinder to measure 50 ml of paint, pour it into the sample tube, hold the sample tube vertically and steadily, the paint begins to flow and spread around, after the paint stabilizes, measure the leveling quality by the diameter of the covered area, the larger the diameter, the better the leveling property.

[0109] The performance test results of the drying speed of the surface coating of Examples 1-7 are shown in Table 3; the performance test results of strength, viscosity, suspension and leveling are shown in Table 4.

[0110] Table 3: Test results of surface coating drying speed

[0111] Performance Testing 3min 5min 6min 7min 10min 30min Example 1 Partially dry Fully dry Fully dry Fully dry Fully dry Fully dry Example 2 Partially dry Fully dry Fully dry Fully dry Fully dry Fully dry Example 3 Partially dry Partially dry Fully dry Fully dry Fully dry Fully dry Example 4 Partially dry Partially dry Fully dry Fully dry Fully dry Fully dry Example 5 Partially dry Fully dry Fully dry Fully dry Fully dry Fully dry Example 6 Partially dry Fully dry Fully dry Fully dry Fully dry Fully dry Example 7 Partially dry Partially dry Fully dry Fully dry Fully dry Fully dry

[0112] Table 4: Strength, viscosity, suspension and leveling test results

[0113]

[0114]

[0115] It can be seen from Table 3 and Table 4 that:

[0116] Through the comparison of Examples 1-7, it can be learned that the casting coating of the present invention is composed of a base coating and a surface coating, and the magnesia powder used in the base coating is mixed with a refractory aggregate of a specific particle size, and the surface coating has an aggregate of a specific particle size. After coating the base coating, the alcohol therein is volatilized by ignition, and continuous and extensive heat can be released, which not only effectively delays the cooling rate of the magnesium-aluminum alloy casting, but also accelerates the curing reaction of the surface coating by utilizing the residual heat of combustion, thereby achieving rapid curing and uniform drying of the coating. Therefore, through the synergistic effect of the base coating and the surface coating, combined with specific raw material ingredients and processes, not only the curing speed and uniformity of the coating are improved, the consistency and reliability of the coating performance are ensured, but also the defects of fast cooling rate and local premature crystallization in the magnesium alloy casting process are effectively solved, thereby improving the overall performance and production efficiency of the casting.

[0117] In order to further make the purpose and effect of the present invention simple and easy to understand, the present invention is further described in conjunction with specific comparative examples.

[0118] Comparative Example 1

[0119] This comparative example is basically the same as Example 1, except that the particle sizes of the refractory aggregate and the surface layer aggregate are different, specifically, in step S1, the particle size of the expanded perlite is 300 mesh; in step S3, the particle size of the mullite powder is 180 mesh.

[0120] Comparative Example 2

[0121] This comparative example is basically the same as Example 1, except that the particle size of the refractory aggregate is different, specifically, in step S1, the particle size of the expanded perlite is 160 mesh.

[0122] Comparative Example 3

[0123] This comparative example is basically the same as Example 1, except that the particle size of the refractory aggregate is different, specifically, in step S1, the particle size of the expanded perlite is 210 mesh.

[0124] Comparative Example 4

[0125] This comparative example is basically the same as Example 1, except that the particle size of the surface layer aggregate is different, specifically, in step S3, the particle size of the mullite powder is 340 mesh.

[0126] Comparative Example 5

[0127] This comparative example is basically the same as Example 1, except that the particle size of the surface layer aggregate is different, specifically, in step S3, the particle size of the mullite powder is 250 mesh.

[0128] Comparative Example 6

[0129] This comparative example is basically the same as Example 1, except that the refractory aggregate raw materials are different. Step S1 is specifically as follows: magnesia powder and hollow microspheres are added into a planetary ball mill, and ball-milled for 45 minutes at a rotation speed of 200 r / min to obtain a bottom aggregate.

[0130] Comparative Example 7

[0131] This comparative example is basically the same as Example 1, except that the refractory aggregate raw materials are different. Step S1 is specifically as follows: magnesia powder and mullite are added into a planetary ball mill, and ball-milled for 45 minutes at a rotation speed of 200 r / min to obtain a bottom aggregate.

[0132] Comparative Example 8

[0133] This comparative example is basically the same as Example 1, except that the refractory aggregate raw materials are different. Step S1 is specifically as follows: magnesia powder and zircon powder are added into a planetary ball mill, and ball-milled for 45 minutes at a rotation speed of 200 r / min to obtain a bottom aggregate.

[0134] The base coating and top coating obtained in Comparative Examples 1-8 were tested using the same performance testing method as the base coating and top coating obtained in Examples 1-7. The performance test results of the drying speed of the top coating are shown in Table 5; the performance test results of strength, viscosity, suspension and leveling are shown in Table 6.

[0135] Table 5: Test results of surface coating drying speed

[0136] Performance Testing 3min 5min 6min 7min 10min 30min Example 1 Partially dry Fully dry Fully dry Fully dry Fully dry Fully dry Comparative Example 1 Not dried Not dried Not dried Not dried Not dried Not dried Comparative Example 2 Not dried Not dried Not dried Not dried Partially dry Fully dry Comparative Example 3 Not dried Not dried Not dried Not dried Not dried Partially dry Comparative Example 4 Not dried Not dried Not dried Not dried Partially dry Partially dry Comparative Example 5 Not dried Not dried Not dried Not dried Not dried Partially dry Comparative Example 6 Not dried Partially dry Fully dry Fully dry Fully dry Fully dry Comparative Example 7 Not dried Not dried Not dried Not dried Partially dry Partially dry Comparative Example 8 Not dried Not dried Not dried Not dried Not dried Partially dry

[0137] Table 6: Strength, viscosity, suspension and leveling test results

[0138]

[0139]

[0140] It can be seen from Table 5 that:

[0141] By comparing Example 1 with Comparative Example 1, it can be learned that by using specific particle sizes for the refractory aggregate in the base coating and the surface aggregate in the surface coating, and the particle size of the refractory aggregate is larger than that of the surface aggregate, the large-particle refractory aggregate in the base coating not only increases the porosity of the coating, but also reduces the density of solid components such as aggregate and binder, so that the same volume of coating can contain more alcohol solvents, thereby releasing more heat and longer residual heat time during combustion, providing the required thermal conditions for the curing of the surface coating, and the small-particle surface aggregate in the surface coating reduces the gaps between aggregate particles in the coating, reduces the content of bound water, and accelerates the drying speed of the coating, so that under the synergistic effect of the base and surface coatings, not only the curing speed and uniformity of the coating are improved, but also the risk of local premature crystallization is effectively avoided by slowing down the cooling rate of the magnesium-aluminum alloy casting, thereby ensuring the high-quality production of the casting.

[0142] It can be seen from Table 6 that:

[0143] By comparing Example 1 with Comparative Example 1, it can be learned that by making the particle size of the refractory aggregate in the base coating larger than the particle size of the surface layer aggregate in the surface coating, the surface layer aggregate can fill the larger gaps left by the refractory aggregate, and can reduce the interface gap between the base coating and the surface coating, so that the interface between the two can form a mechanical interlocking, increase the friction between the base layer and the surface layer, thereby improving the overall density and bonding strength, helping to form an overall uniform coating and reduce local defects.

[0144] It can be seen from Table 5 and Table 6 that:

[0145] By comparing Example 1 with Comparative Examples 2-5, it can be learned that the appropriate refractory aggregate particle size and surface layer aggregate particle size can ensure the performance of the coating and the quality of the casting. In the base coating, if the refractory aggregate particle size is too large, the pore structure will be too coarse, affecting the storage and release of alcohol solvents, resulting in insufficient heat release, slowing down the curing and drying of the surface coating; if the particle size is not large enough, the porosity and solvent storage capacity will be limited, and the cooling rate of the casting cannot be effectively delayed, and the promotion effect on the curing of the surface coating will be weakened. In the surface coating, if the aggregate particle size is too small, the coating will be too viscous, increase the surface area, absorb more water, and delay drying; if the particle size is not small enough, the porosity will be increased, the bound water content will increase, and the drying will also be delayed, and the surface roughness of the coating may increase, affecting the surface quality of the casting and the overall strength of the coating.

[0146] By comparing Example 1 with Comparative Example 6, it can be learned that by using expanded perlite with a porous structure or hollow microspheres with a hollow structure as refractory aggregates in the primer, more alcohol solvents can be effectively stored by utilizing their unique structure. When combustion occurs, it can not only quickly heat up and release a large amount of heat, but also because of its lightweight characteristics, the heat transfer is more uniform, reducing the impact of temperature gradients on castings, and helping to form a more stable primer, thereby improving the mechanical interlocking with the surface coating and enhancing the bonding strength of the overall coating.

[0147] By comparing Example 1 with Comparative Examples 7 and 8, it can be seen that although mullite powder and zircon powder have good high temperature resistance, they are usually dense solid particles with limited ability to store alcohol solvents, making it difficult to effectively slow down the cooling rate of the casting. The additional heat provided during the combustion process is small and insufficient to significantly promote the drying of the surface coating, resulting in a decrease in the drying rate of the surface coating. In addition, they cannot effectively participate in the interaction between the base coating and the surface coating as effectively as expanded perlite or hollow microspheres, thereby reducing the bonding strength between the two layers of coating.

[0148] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0149] The above is based on the ideal embodiment of the present invention. Through the above description, it is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.

[0150] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A magnesium-aluminum alloy casting coating, comprising: The base coating and the surface coating are characterized in that the mass ratio of the base coating to the surface coating is 1:1-2; The primer comprises the following raw materials in parts by weight: The surface coating comprises the following raw materials in parts by weight: The bottom layer aggregate is a mixed aggregate of magnesia powder and refractory aggregate, and the particle size of the refractory aggregate is larger than that of the surface layer aggregate.

2. The magnesium-aluminum alloy casting coating according to claim 1, characterized in that: The refractory aggregate accounts for 30-50% of the total amount of the bottom aggregate; the refractory aggregate is one of expanded perlite, hollow microspheres, mullite or zircon powder; the particle size of the refractory aggregate is 170-200 meshes.

3. The magnesium-aluminum alloy casting coating according to claim 1, characterized in that: The surface aggregate is one of mullite powder, corundum powder or zircon powder; the particle size of the surface aggregate is 270-325 meshes.

4. The magnesium-aluminum alloy casting coating according to claim 1, characterized in that: The alcohol solvent is one of methanol or ethanol.

5. The magnesium-aluminum alloy casting coating according to claim 1, characterized in that: The leveling agent is one of organic silicone oil, polyacrylate or polysiloxane.

6. The magnesium-aluminum alloy casting coating according to claim 1, characterized in that: The dispersant is one of polyethylene glycol and sodium polyacrylate.

7. The magnesium-aluminum alloy casting coating according to claim 1, characterized in that: The binder is one of aluminum dihydrogen phosphate or phenolic resin.

8. The magnesium-aluminum alloy casting coating according to claim 1, characterized in that: The suspending agent is one of sodium bentonite, sodium carboxymethyl cellulose or hydroxyethyl cellulose.

9. A process for preparing a magnesium-aluminum alloy casting coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, adding magnesia powder and refractory aggregate into a planetary ball mill for ball milling and mixing to obtain bottom aggregate; S2, adding the bottom aggregate, alcohol solvent, leveling agent and dispersant into a planetary ball mill for ball milling and mixing to obtain a bottom coating; S3. Add the surface layer aggregate, binder, suspending agent, dispersant and water into a planetary ball mill for wet grinding and mixing to obtain the surface layer coating.

10. The process for preparing a magnesium-aluminum alloy casting coating according to claim 9, characterized in that: In the step S1 and the step S2, the mixing speed of the ball mill is 180-220 r / min, and the mixing time is 30-50 min; in the step S3, the mixing speed of the wet mill is 200-240 r / min, and the mixing time is 30-60 min.